The occupancy of Great Indian Bustard (Ardeotis nigriceps) using local people’s knowledge in the Deccan Plateau, Karnataka, India - P. RAMESH KUMAR; D. DEEPAK; HONNAVALLI N. KUMARA; S. BABU (Society for Indonesian Biodiversity, 2023)
Abstract. Kumar PR, Deepak D, Kumara HN, Babu A. 2023. The occupancy of Great Indian Bustard (Ardeotis nigriceps) using local people’s knowledge in the Deccan Plateau, Karnataka, India. Biodiversitas 24: 1400-1407. The Great Indian Bustard (Ardeotis nigriceps) (GIB) is a critically endangered species that went extinct in most of its geographical range and is facing global extinction risk. The southernmost population of this bird at present is in Siruguppa taluk of Bellary district in Karnataka State, India. Except for a few sight records, data is not available on any aspect of the species in the state. We collected sightings of GIB from the local people for an area of 359 km2. We modeled the probability of occurrence of GIB for the study site and associated it with the habitat parameters. Keeping the findings of the occupancy, we explored the study site for the GIB. The results showed that tree density and length of the metal road influenced the occupancy positively, while the number of villages and period of land use influenced it negatively. Nearly 30% of the grids were predicted to have high probability of detecting GIB in this landscape. We had 115 detections of GIB and recorded them in 70% of the grid cells where local people reported the sightings of GIBs. The use of local people’s knowledge is beneficial and less expensive for the species like GIB for the initial exploration and also to monitor them at a landscape level.